2014
DOI: 10.1016/j.vhri.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Costo Utilidad de Colágena Polivinil-Pirrolidona en el Tratamiento de Osteartrosis de Rodilla en México

Abstract: This is the first economic evaluation of a new medication developed in Mexico and conducted partially with local data. The results of this study allow concluding that collagen-PVP is deemed as the dominant alternative compared with NSAIDs in the treatment of knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This result is in agreement with the low incidence of AEs attributable to IA therapies reported in clinical trials in knee OA, with the main AEs being postinjection pain and swelling, as in our study [ 38 ]. Moreover, we previously reported that polymerized-type I collagen was a dominant cost-benefit alternative compared with NSAIDs in the treatment of symptomatic knee OA [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with the low incidence of AEs attributable to IA therapies reported in clinical trials in knee OA, with the main AEs being postinjection pain and swelling, as in our study [ 38 ]. Moreover, we previously reported that polymerized-type I collagen was a dominant cost-benefit alternative compared with NSAIDs in the treatment of symptomatic knee OA [ 39 ].…”
Section: Discussionmentioning
confidence: 99%